Transient Liquid Phase Bonding of Semi-Solid Metal 7075 Aluminum Alloy using ZA27 Zinc Alloy Interlayer - Chaiyoot Meengam; Yongyuth Dunyakul; Dech Maunkhaw; Suppachai Chainarong (Metals, 2018)
Transient Liquid Phase Bonding (TLPB) process of semi-solid metal 7075 aluminum alloys (SSM7075) using 50 μm thick of ZA27 zinc alloys as interlayers for the experiment were carried out under bonding temperatures of 480 and 540 °C and bonding times of 30, 60, 90 and 120 min respectively. In the bonding zone, the semi-solid state of ZA27 zinc alloy interlayers were diffused into the SSM7075 aluminum alloy. Examination of the bonding zone using Scanning Electron Microscope (SEM) and Energy-dispersive X-ray spectroscopy (EDS) showed that the precipitation of the intermetallic compound of η(Zn–Al–Cu), β(Al2Mg3Zn3), T′(Zn10Al35Cu55) and MgZn2 were formed in the bonding zone. The better homogenized microstructure in the bonding zone was formed when increasing bonding time and bonding temperature. The highest bonding strength was recorded at 17.44 MPa and average hardness was at 87.67 HV with the bonding time of 120 min and temperature at 540 °C. Statistically, the coefficient of determination analysis of bonding strength data was at 99.1%.